The effect of pottasium (K) on the development of scarlet mite (Brevipalpus phoenicis Geijske) population at tea crop (Camellia sinensis (L.) O. Kuntze) - Sucherman, Odih (Research Institute for Tea and Cinchona, 2014)
A research experiment to know the effect of pottasium on the population development of scarlet mite and growth of young tea was carried out. The experiment was conducted at Green House of Plant Protection Department Research Institute Tea and Cinchona GamÂbung, Bandung, West Java, from December 2011 until July 2012. The soil type used is Andisol and altitude is 1.250 m above sea level. The treatments were potassium fertilizer appliÂcations of 0, 30, 40 (standars treatment), 50, 60, 70, 80, 90, and 100 kg K20/ha/year; in which the 0 dosage was used as untreated control. The result of the experiment showed that: pottasium fertilizer at the dosage 70 kg K2O/ha/year to 100 kg K2O/ha/year reasonably effective in pressuring the development of the population development of scarlet mite and increasing the number of leaves as indication of rising class seedlings on young tea. Pottasium fertilizer at the medium dosage 70 kg K2O/haÂ/year reasonably effective in pressuring the development of the population development of scarlet mite and increasing the number of leaves as indication of rising class seedlings, when compared to the standards (40 kg/ha/y) and control dose on young tea.